2014
DOI: 10.1159/000360363
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass Gain Predicts Estimated GFR Decline in a Relatively Healthy Korean Population

Abstract: Background: Previous studies have shown that obesity is a risk factor for estimated glomerular filtration rate (eGFR) decline and chronic kidney disease (CKD). However, the relationship between fat mass directly measured by bioimpedance analysis and eGFR is not well known. Methods: We analyzed 21,859 participants without CKD at baseline who underwent two health checkups at a 5-year interval during 2002-2009. Fat mass was measured by Inbody 3.0 (Biospace, Seoul, Korea). eGFR decline was defined as eGFR <60 ml/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, another study observed decline in GFR in later life. [35] Such observation necessitates further work up to follow up GFR in all study populations and also necessitate weight reduction programs to minimize the risk of the gradual decline of renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study observed decline in GFR in later life. [35] Such observation necessitates further work up to follow up GFR in all study populations and also necessitate weight reduction programs to minimize the risk of the gradual decline of renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between body fat and renal prognosis has been studied several times. Body fat mass gains measured by BIA are independently associated with a decrease of eGFR <60 mL/min/1.73 m 2 in a relatively healthy Korean population 4 . In CKD patients, the VFA‐to‐SFA ratio is a risk factor of reduced kidney function 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Body fat mass gains measured by BIA are independently associated with a decrease of eGFR <60 mL/min/1.73 m 2 in a relatively healthy Korean population. 4 In CKD patients, the VFAto-SFA ratio is a risk factor of reduced kidney function. 8 However, this previous study had limited number of patients and did not consider age and sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations